Combination of noninvasive brain stimulation with pharmacotherapy. (January 2011) - Brunoni, Andre Russowsky; Valim, Clarissa; Fregni, Felipe
Noninvasive brain stimulation (NIBS) techniques are being increasingly investigated as a therapeutic approach for neuropsychiatric disorders. One method is to combine NIBS with pharmacotherapy to enhance the clinical effects or avoid an increase in drug dosages to decrease the incidence of side effects. However, few studies to date have investigated the relative and combined efficacy of NIBS with pharmacotherapy. Based on a literature review of previous studies and meta-analyses for major depression, we identified four randomized, controlled trials that tested the combination of NIBS with a new drug and two trials that directly compared NIBS versus pharmacotherapy. There was no study designed to address the relative efficacy of each intervention against placebo and against combined therapy. We discuss the methods and rationale of NIBS–pharmacotherapy trials, addressing some methodological aspects, including factorial design, recruitment, blinding, blinding assessment, placebo effect and quantitative aspects, such as power analysis, statistics and interaction effects. Our review of the methodology underlying NIBS–drug trials provides insights for the further clinical research development of NIBS in major depression.